Aplicación de brassinoesteroide para promover el crecimiento del brote en injerto de rosa (Rosa sp.) - Jara Gómez, José Washington (2012)
The present investigation had for object to determine the brassinoesteroide application to promote the growth of the bud in rose implant (Rosa sp.). The utilized hormone was Brassinolina and its applied doses they were Brassinolina 1 ml.L-1 of water, Brassinolina 1,5 ml.L-1 of water, Brassinolina 2 ml.L-1 of water. The investigative work was carried out in the canton Patate county of the Tungurahua, in the sector Chalpi, property of Mr. José Washington Jara Gómez. The field works were carried out under conditions of ambient temperature 190C, 50% of relative humidity, heliophany 1.760 hours of average yearly and 2.291 m.s.n.m. The design experimental employee was a D.B.C.A. with 4 treatments and 5 repetitions, the taking of data was made during 60 days, to which were carried out the statistical analysis by means of Statistical Analysis System (SAS). The procedure ANOVA was used for the variance analysis and test of Tukey (0,05). He was also carried out an economic analysis of each treatment in study: Application cost, total entrance, balance of income, relationship benefit/cost and production/plants cost. Of the results he settles down that the best treatment is the T3 (Brassinolina 2 ml.L-1 of water), because it stimulates the growth of the bud of the implant in rose (Rosa sp.) until the 49,32 centimeters of longitude. The treatment T3 (Brassinolina 2 ml.L-1 of water) it is the one that presented bigger benefit/cost with a value of 0,96 and the treatment T4 (Witness) it presented the drop in value of 0,23 in benefit/cost. To obtain implant buds in rose (Rosa sp.) of a longitude of 49,32 centimeters, it is recommended to apply Brassinolina 2 ml.L-1 of water.